Resistant starch from high amylose maize (HAM‐RS2) and Dietary butyrate reduce abdominal fat by a different apparent mechanism - Vidrine, Kirk; Ye, Jianping; Martin, Roy J.; McCutcheon, Kathleen L.; Raggio, Anne M.; Pelkman, Christine; Durham, Holiday A.; Zhou, June; Senevirathne, Reshani N.; Williams, Cathy; Greenway, Frank; Finley, John; et al. (Obesity (Silver Spring, Md.), 2014)
Objective Obesity is a health concern. Resistant starch (RS) type 2 from high‐amylose maize (HAM‐RS2) and dietary sodium butyrate (SB) reduce abdominal fat in rodents. RS treatment is associated with increased gut hormones peptide YY (PYY) and glucagon‐like peptide 1 (GLP‐1), but it is not known if SB increases these hormones. Design and Methods This was investigated in a 2 × 2 rat study with HAM‐RS2 (0 or 28% weight) and dietary sodium butyrate (0 and 3.2%) resulting in isocaloric treatments: energy control (EC), sodium butyrate (SB), HAM‐RS2 (RS), and the combination (SBRS). Results RS and SB reduced abdominal fat and the combination reduced abdominal fat compared to SB and RS. RS was associated with increased fermentation in the cecum. Serum PYY and GLP‐1 total were increased with RS treatment. RS treatment was associated with increased cecal butyrate produced from fermentation of RS, but there was no cecal increase for dietary SB. Conclusions SB after its absorption into the blood appears to not affect production of PYY and GLP‐1, while butyrate from fermentation in the cecum promotes increased PYY and GLP‐1. Future studies with lower doses of RS and SB are warranted and the combination may be beneficial for human health.